2020
DOI: 10.1007/s12325-020-01262-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Switch Patterns and Healthcare Costs in Biologic-Naive Patients with Psoriatic Arthritis

Abstract: Introduction: We compared treatment switch patterns and healthcare costs among biologicnaive patients with psoriatic arthritis (PsA) who initiated apremilast or biologics. Methods: A 1:2 propensity score match was used to adjust administrative claims data for adults initiating apremilast or biologics from January 1, 2014, to September 30, 2016, for possible selection bias. Patients had at least 12 months of pre-and post-index continuous enrollment in the Optum Clinformatics TM Data Mart database. Outcomes incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Switching rates found in the current study are also generally consistent with those reported in the literature 15,18 . In a recent study by Wu et al, assessing treatment patterns in PsA patients treated with bDMARDs (TNFi and non-TNFi) versus apremilast, authors reported a 33.3% switching rate at 2 years after treatment initiation in the bDMARDs cohort 15 the switching rate among PsA patients was 32.3% at 2 years in the current study. Similarly, the one year switching rate found in the current study among the subsample of RA patients (21.9%) is also generally in line with the rates reported in the literature, ranging between 11 and 18%, although closer to the upper end of the spectrum [19][20][21] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Switching rates found in the current study are also generally consistent with those reported in the literature 15,18 . In a recent study by Wu et al, assessing treatment patterns in PsA patients treated with bDMARDs (TNFi and non-TNFi) versus apremilast, authors reported a 33.3% switching rate at 2 years after treatment initiation in the bDMARDs cohort 15 the switching rate among PsA patients was 32.3% at 2 years in the current study. Similarly, the one year switching rate found in the current study among the subsample of RA patients (21.9%) is also generally in line with the rates reported in the literature, ranging between 11 and 18%, although closer to the upper end of the spectrum [19][20][21] .…”
Section: Discussionsupporting
confidence: 92%
“…However, the high proportion of RA and PsA patients initiating first-line advanced treatment on adalimumab and etanercept is consistent with the literature. Adalimumab and etanercept are well-established TNFi and generally reported as the most common treatments initiated among patients starting advanced treatments [14][15][16][17] . Switching rates found in the current study are also generally consistent with those reported in the literature 15,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-related treatments include antineoplastic agents, adjunctive therapies, and any other US Federal Drug Administration (FDA)-approved treatment for conditions caused by cancer or its treatment [ 24 ]. The costs utilized in this analysis reflects standardized costs calculated based on a proprietary Optum algorithm that reflects adjustment of allowable payment amounts sourced from the claim forms to estimate standardized costs that reduce potential local/regional or payer/plan differences across individual hospitals and providers and enable national normalization of costs for better comparison across patients, data sources, and geographic regions [ 25 – 27 ]. All dollar estimates were inflated to 2020 dollars using an Optum-provided inflation factor based on the Medical Care Component of the Consumer Price Index (CPI).…”
Section: Methodsmentioning
confidence: 99%
“…A substantial proportion of patients with PsA are inadequately treated with currently available therapeutic options; many of these medications have safety concerns and have inconvenient dosing, and few patients reach treatment targets, such as achievement of minimal disease activity (MDA). This results in disease progression and disability, frequent medication switching, and higher overall treatment costs 5 6. Therapies with new modes of action that are safe, effective and have convenient dosing are needed to control the spectrum of disease manifestations and improve the quality of life of patients with PsA as another option for treatment, including in those who do not respond to other modalities 7 8…”
Section: Introductionmentioning
confidence: 99%